(untitled) (Journal of Management and Social Sciences, 2017)
Abstract Natural resources endowment is expected to boost wealth and purchasing power in resource endowed economies. It is expected that resource availability should be able to drive investment and consequently boost growth in these economies. However, experiences with some resource - rich economies suggest that resource endowment may not be a blessing and can actually be categorized as a curse. To this end therefore, this study investigates the relationship between resource endowment and economic growth using nine resource-rich African countries as a case study. The study used the fixed effect model with cross section as well as time dummy variables. The study did not establish the significant positive impact of resource extraction on economic growth in these economies and therefore concludes that resource curse is indeed true in countries under the study. This paper recommends that as resources’ booms are occurring, governments of resource rich economies can channel the surplus funds into the development of other sectors of the economy to enhance their competitiveness and capacity and boost their productivity so that when resources rents becomes low, other sector can cushion the effect. This is a form of diversification for a resource rich economy among others.